In-silico Analysis Potential Of Curcuma zedoaria As A Candidate For Degenerative Disease Therapy - Fitria Dwi Damayanti; Risma Ayu Setiawan; Tri Luthfiana Maretha; Trikxy Viori Andhani; Faiznanda Awwaluddin; Resi Puguh Prihantono; Ahmad Shobrun Jamil (EKSAKTA: Journal of Sciences and Data Analysis, 2022)
Indonesia has a high and diverse biodiversity, particularly in plant species. There are numerous advantages to using various plants that grow in Indonesia. Indonesia is also known for its abundance of spices and other natural resources. Rapid research is required in the use of this plant in order for bio-based products to be widely accepted. Using in-silico predictions by utilizing meta data provided by several credible sites is one of the important rapid methods in analyzing the benefits of the chemical content of Curcuma zedoaria (Temu putih). The goal of this in-silico analysis-based study is to gain an understanding of the pharmacology of a plant known as potency simplicia Curcuma zedoaria. Analyzing metadata from various sources is the research method. Prediction of absorption, distribution, metabolism, and excretion (ADME) was obtained from http://www.swissadme.ch/. The prediction of target proteins for phytochemical compounds of Curcuma zedoaria is available at http://www.swisstargetprediction.ch/, while the construction of active protein networks and interactions after induction of compounds contained in Curcuma zedoaria rhizome is available at https://string-db.org. According to the in-silico analysis performed with some of the software mentioned above, the rhizome of Curcuma zedoaria (Temu Putih) contains 71 active compounds, 64 of which are highly bioavailable. According to in-silico research, Curcuma zedoaria (Temu Putih) contains curcumin compounds (diarylheptanoid) and its derivatives have antioxidant activity, which functions to prevent stress from physiological stimulation that can increase the number of leukocytes.